2017
DOI: 10.1007/s11255-017-1757-x
|View full text |Cite
|
Sign up to set email alerts
|

Emodin ameliorates renal fibrosis in rats via TGF-β1/Smad signaling pathway and function study of Smurf 2

Abstract: Emodin showed an anti-fibrosis effect in surgery-induced renal fibrotic rats. And this effect was potentially achieved via down-regulating expressions of TGF-β1 and Smurf 2 and up-regulating Smad7 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…We used in this work the relatively novel biomarkers TGF-β1, which is used as biomarker in cardiovascular diseases (Mukherji et al 2017), and lately as a biomarker in surgery-induced renal fibrosis in rat (Ma et al 2018). Here, we found that its concentration in plasma is significantly increased in CP-induced nephrotoxicity, and that sesamin significantly ameliorated that action.…”
Section: Discussionmentioning
confidence: 87%
“…We used in this work the relatively novel biomarkers TGF-β1, which is used as biomarker in cardiovascular diseases (Mukherji et al 2017), and lately as a biomarker in surgery-induced renal fibrosis in rat (Ma et al 2018). Here, we found that its concentration in plasma is significantly increased in CP-induced nephrotoxicity, and that sesamin significantly ameliorated that action.…”
Section: Discussionmentioning
confidence: 87%
“…Salvia miltiorrhiza Bunge, Astragalus mongholicus Bunge, and Rheum palmatum L.) and active components (e.g. tanshinone, salvianolic acid, and emodin) reportedly possess antirenal fibrosis effect (Wang et al, 2015;Ma et al, 2017;Zhang et al, 2018). Unlike the one drug-one target concept of Western medicine, TCM emphasizes that the human body is an organic whole.…”
Section: Introductionmentioning
confidence: 99%
“…6 Recent studies have indicated that TGF-β1 plays an important role in the progression of renal fibrosis. 7,8 In addition, Higgins et al have found that TGF-β1 signaling pathway plays a critical role during the induction of renal fibrosis. 9 Besides, it has been previously reported that activation of TGF-β1 signaling pathway can promote EMT process during the metastasis of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%